STRATEGI PEMASARAN GUNA MENINGKTKAN DAYA SAING PADA MASA PANDEMI COVID-19 (STUDI KASUS DI TANI JIWO HOSTEL BANJARNEGARA) - Ratna Wijayanti; Wahab Wahab; Anita Fitriana; M. Shofiyuddin (Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to find out what marketing strategies are best used by Tani Jiwo Hostel during the Covid-19 pandemic. The management who became the sample in this study amounted to 5 people, while the consumers who were the samples in this study were some visitors within 1 month who had visited Tani Jiwo Hostel. This research uses External Internal Matrix (IE), Strength, Weakness, Opportunity and Threat Matrix (SWOT) and Quantitative Strategic Planning Matrix (QSPM). The IE and SWOT matrices are used to plan alternative strategies, while the QSPM matrix is used to determine priority strategies. The results showed that the strategies that could be applied were market penetration strategies, market development strategies, and product/service development strategies